Electron impact ionization cross sections of C2H4 molecule - Rajeev Kumar; Pawan Kumar Sharma (Chemical Physics Impact, 2020)
In this paper, we have investigated partial and total integral ionization cross sections of C2H4 molecule by Jain-Khare semiempirical approach during the electron impact. They show good agreement with available data. Besides integral ionization cross sections, the first time we have evaluated its partial and total single and double differential cross sections. No other results are available for single differential cross sections and double differential cross sections to compare the present results calculated.